Psychological Dimensions and Implications of Adolescent Sexual and Reproductive Health: A Scoping Review of Existing Evidence - Yessy Syahradesi; Fika Lestari; Siska Putri Belangi; Dina Andriani; Nur Triningtias Putri (Indonesian Journal of Global Health Research, 2026)
Adolescence is a critical developmental period marked by complex biological, psychological, and social changes that influence sexual and reproductive health (SRH) behaviors. Psychological factors such as attitudes, self-efficacy, mental health, and communication skills play a crucial role in shaping adolescents’ sexual decision-making and preventive behaviors. However, evidence on intervention-based strategies integrating psychological perspectives remains fragmented. This scoping review aimed to map and synthesize intervention-based evidence on adolescent sexual and reproductive health with a focus on psychological perspectives and implications. This review followed the Arksey and O’Malley framework and adhered to PRISMA-ScR guidelines. A comprehensive search was conducted in PubMed, Scopus, Web of Science, CINAHL, and Google Scholar for studies published between 2019 and 2025, identifying 245 records. After screening and eligibility assessment, 11 studies were included. Eligible studies included randomized controlled trials and quasi-experimental designs involving adolescents aged 10-19 years and interventions incorporating psychological outcomes. Data were extracted and synthesized descriptively. Eleven intervention studies from diverse global settings were included. School-based, digital, and family-based interventions consistently improved adolescents’ SRH knowledge, attitudes, self-efficacy, communication skills, and preventive behaviors. Theory-driven and multi-component interventions demonstrated the greatest effectiveness. Psychological and psychosocial factors, including mental health, social norms, and parent-adolescent communication, significantly influenced SRH outcomes. However, gaps were identified in low- and middle-income countries and in long-term behavioral and mental health outcomes. Psychologically informed, theory-based, and multi-component interventions are effective strategies to promote healthy sexual and reproductive behaviors among adolescents.